Indicative methodology for identifying affiliation in the public procurement system as a tool for ensuring the economic security of the regional economic complex - Tat'yana V. MOKEEVA; Marina V. IVANOVA; Varvara V. NESTERENKO; Anastasiya A. PAPSHEVA (National Interests Priorities and Security, 2026)
Subject. This article discusses the problem of identifying the affiliation of participants in the Russian public procurement system as a threat to the economic security of the regional economic complex. Objectives. The study aims to develop, verify and test a two-level indicative methodology for identifying the affiliation of participants in the contract system, suitable for various types of regulatory authorities use. Methods. For the study, we used the methods comparative analysis, expert assessments, digital profiling of participants and an indicative risk analysis. Results. The article proposes a two-level methodology for identifying the affiliation of participants in the contract system. Testing on a sample of sixteen real government contracts has confirmed its practical applicability. Conclusions. For the first time, the work formalizes the economic content of the affiliation concept in relation to the contract system. The assessment of the economic impact of the implementation showed the potential to reduce the complexity of control measures while expanding the coverage of the audited purchases. The methodology ensures the transition of control activities in the field of public procurement from a retrospective audit to preventive risk monitoring.